Optimal step doses for drug provocation tests to prove beta‐lactam hypersensitivity. Issue 4 (23rd November 2016) - Chiriac, A.‐M.; Rerkpattanapipat, T.; Bousquet, P.‐J.; Molinari, N.; Demoly, P.
Abstract: Background: Drug provocation tests (DPT) are commonly performed as part of β‐lactam (BL) allergy workup, in case of negative skin tests (ST) and in the absence of contraindications. The recommendations of learned societies have created a frame for DPT performance, but protocols vary widely between centres, generating various hypothesis‐driven protocols (i.e. empirical dosing, driven by both safety concerns and practical aspects). Methods: The primary objective of this retrospective analysis was to detect eliciting dose thresholds (reactive doses) during BL DPT, using the survival analysis method, in order to suggest optimal step doses. Our secondary objective was to evaluate the safety of our 30‐min incremental 1‐day protocol. The study included all the patients explored in the Allergy Unit of the University Hospital of Montpellier (France), between September 1996 and July 2015 for a suspicion of drug hypersensitivity reaction to BLs, with negative ST and positive DPT. Results: During the study period, 182 positive DPT (accounting for 171 hypersensitive patients) were analysed. We identified eliciting thresholds, and we suggest the following steps for DPT to BLs: 5–15–30–50% of daily therapeutic dose (with additional lower steps for index reactions of anaphylaxis). We confirm the safety of 1‐day protocol for immediate and mild nonimmediate reactors, for both children and adults, with a surveillance period of 2 h after the last administered dose, and a prolonged surveillance after discharge of 48 h. Conclusion: This data‐driven approach in designing DPT protocols is a step forward in improving DPT standardization, starting with the most frequently tested drugs, BL antibiotics.